1987
DOI: 10.1038/328077a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytotoxic T-cell responses in vivo in the absence of CD4 helper cells

Abstract: Cytotoxic T lymphocytes (CTL) seem to provide the major line of defence against many viruses. CTL effector functions are mediated primarily by cells carrying the CD8 (Ly-2) antigen (CD8+ cells) and are triggered by interactions of the T-cell receptor with an antigenic complex, often termed 'self plus X', composed of viral determinants in association with class I molecules of the major histocompatibility complex (MHC). The mechanism(s) of induction of virus-specific CTL in vivo is poorly understood, but data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
184
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(199 citation statements)
references
References 0 publications
13
184
1
Order By: Relevance
“…First, experiments in animal models have shown that CD4 + helper cells are not required for an anti-VV CTL response. 55 Furthermore, CTL responses to VV and other viruses have been observed in CTLA-4 transgenic mice, suggesting that CD80 expression by APC is not an absolute requirement for the induction of a CTL response. 56,57 In addition, it has been shown that the costimulatory molecule CD86 (which was not affected by VV, Figure 5) can drive a CTL response in a MHC restricted manner.…”
Section: Discussionmentioning
confidence: 99%
“…First, experiments in animal models have shown that CD4 + helper cells are not required for an anti-VV CTL response. 55 Furthermore, CTL responses to VV and other viruses have been observed in CTLA-4 transgenic mice, suggesting that CD80 expression by APC is not an absolute requirement for the induction of a CTL response. 56,57 In addition, it has been shown that the costimulatory molecule CD86 (which was not affected by VV, Figure 5) can drive a CTL response in a MHC restricted manner.…”
Section: Discussionmentioning
confidence: 99%
“…Since, however, after long-term depletion of the CD4 subset, the lymphocyte population was composed of a CD8 subset and of a new subset with the phenotype CD4-CD8-(recall Fig. 2), it became necessary to also consider the possibility that the antiviral function was performed by this new subset and not, as one would anticipate from published experience (19)(20)(21)(22), by CD8' effector cells generated independently of the CD4 subset . Elimination in vitro of the CD8 subset and transfer of the resulting purified CD4-CD8-population (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have given examples for an autonomy in vivo of the CD8 subset in viral infection models involving a depletion of the CD4 subset (19)(20)(21)(22), which implies that cooperation of CD4+ helper T lymphocytes is not essential for initiating a CD8 subset-mediated immune response. Whether such a response can last long enough to also maintain a long-term control and eosin.…”
mentioning
confidence: 99%
“…The most effective cells for eliminating tumour cells are CD8 + cytotoxic T lymphocytes (CTLs) that specifically recognize the tumour antigens presented in association with class I MHC molecules 1. To prime and activate CTLs in a tumour environment, dendritic cells (DCs) are key cells that uptake tumour proteins, process them into peptide fragments containing immunodominant epitope(s), and present them on their surface associated with antigen‐presenting class I MHC molecule(s) for the activation of specific T‐cell immunity 2, 3…”
Section: Introductionmentioning
confidence: 99%